Images of the Female Scientist from the Lithuanian Teenagers Point of View - Urbonienė, Aistė (Sociologija. Mintis ir veiksmas, 2009)
Sector of technological and physical sciences is exceptionally male professional area and it is rather difficult for women to become professionals in this field. Professional gender stereotypes is one of the main reasons that impact attitudes towards women in this male area. This paper aims to identify images of female scientist in the field of technological and physical sciences among Lithuanian teenagers. The sample consisted of 1398 respondents (58 % females and 42 % males). Qualitative content analysis was used in this study. The study showed that four images of the female scientist are dominating among teenagers: attractive and competent scientist, unattractive scientist, sexually looking scientist and neutrally looking scientist. The results of the empirical analysis indicated that stereotypical evaluations and even discriminating attitudes are more characteristic for the male respondents while female respondents use to evaluate the female scientist neutrally or even idealized.